Geopolitics of the European Rule of Law — Lessons from Ukraine and the Western Balkans - Elise Bernard (Intereconomics)
Abstract Several opportunities arise for rule of law promoters: to reclaim the security discourse; to explain EU enlargement through the commitment to the rule of law; and consequently, to develop a strategy to influence opponents of enlargement.